Does it hold weight? The perceived effects of contraceptive use on weight status in females: A mixed-methods study - Leonie Bass; Tamara Prostináková; Kathelijne Gabrielle Silang; Alyssia Griffiths-Gray; Stephen McQuilliam; Elizabeth Mahon; Amy Whitehead; Kelsie Olivia Johnson (PLoS ONE, 2025)
Purpose To examine females’ perceived effects of contraceptive use on weight management and to identify potential confounding factors that may contribute to perceived weight changes across their lifespan. Methods Three hundred and fifteen predominantly UK-based females completed a questionnaire assessing the prevalence and type of current and previous contraceptive use, reasons for use, side effects experienced, and perceived effects on weight. Twenty-five participants who reported contraceptive use subsequently completed timeline interviews to gain deeper insight into the perceived impact of contraception on weight status and to identify contextual or lifestyle factors that may have contributed to perceived weight-management difficulties. Results Contraceptive use prevalence was 88% among respondents, with 38% using a contraceptive method at the time of data collection. Forty-two percent reported greater difficulty managing their weight while using hormonal contraception compared with their natural menstrual cycle. In follow-up interviews, depot medroxyprogesterone acetate (DMPA) was consistently identified as the method most associated with difficulties in weight management. However, most participants attributed weight-related challenges to broader life circumstances, such as moving away from home, relationship changes, and stress, rather than contraceptive use alone. Conclusion Although 42% of females reported difficulty managing their weight while using contraception, these perceptions often reflected lifestyle factors rather than physiological effects of the contraceptive itself. Clinicians, coaches, and recreationally active females should consider the most appropriate contraceptive type for their circumstances and also reflect on life status and current events as potential contributors to perceived weight management struggles or weight gain . Individuals may want to consider alternative methods if they are initially affected by DMPA.